(untitled) (Analysis in Theory and Applications, 2014)
In this paper, we will use a method of sharp maximal function approach to show the boundedness of commutator [b,T_R^δ] by Bochner-Riesz operators and the function b on weighted Morrey spaces L^p,κ(ω) under appropriate conditions on the weight ω, where b belongs to Lipschitz space or weighted Lipschitz space.